Peran Mata Kuliah Modul Nusantara dalam Mengenal Upacara Ulun Ondot Suku Dayak melalui Program Pertukaran Mahasiswa Merdeka - Juli Darmawati Zega; Silva Riska Natalia Simanjuntak; Chistian Sitepu (Journal on Education, 2023)
The Nusantara Module is one of the compulsory subjects for students participating in the Independent Student Exchange program. The Archipelago Module is a series of activities that focus on creating a comprehensive understanding and aim to introduce the cultural richness of the Archipelago from various aspects. The purpose of this research is to find out how the Nusantara Module course recognizes the Ulun Ondot ceremony of the Dayak tribe. This study uses a qualitative approach. The subject of this research is the Dayak people who live in Sekatak Buji Village, Sekatak District, Bulungan Regency, North Kalimantan Province. Collecting data using the method of observation, interviews, and documentation. The results of the research show that the Nusantara Module course has a role in getting to know Dayak culture, especially the Ulun Undot Ceremony for Inbound Students through: directly observing the Ulun Undot ceremony of the Dayak tribe and knowing that the Ulun Ondot custom is a cultural heritage of the Dayak tribe.